Deep phenotyping classical galactosemia: clinical outcomes and biochemical markers. Issue 1 (29th January 2020) - Welsink-Karssies, Mendy M; Ferdinandusse, Sacha; Geurtsen, Gert J; Hollak, Carla E M; Huidekoper, Hidde H; Janssen, Mirian C H; Langendonk, Janneke G; van der Lee, Johanna H; O'Flaherty, Roisin; Oostrom, Kim J; Roosendaal, Stefan D; Rubio-Gozalbo, M Estela; et al.
Abstract: Early diagnosis and dietary treatment do not prevent long-term complications, which mostly affect the central nervous system in classical galactosemia patients. The clinical outcome of patients is highly variable, and there is an urgent need for prognostic biomarkers. The aim of this study was first to increase knowledge on the natural history of classical galactosemia by studying a cohort of patients with varying geno- and phenotypes and second to study the association between clinical outcomes and two possible prognostic biomarkers. In addition, the association between abnormalities on brain MRI and clinical outcomes was investigated. Classical galactosemia patients visiting the galactosemia expertise outpatient clinic of the Amsterdam University Medical Centre were evaluated according to the International Classical Galactosemia guideline with the addition of an examination by a neurologist, serum immunoglobulin G N -glycan profiling and a brain MRI. The biomarkers of interest were galactose-1-phosphate levels and N -glycan profiles, and the clinical outcomes studied were intellectual outcome and the presence or absence of movement disorders and/or primary ovarian insufficiency. Data of 56 classical galactosemia patients are reported. The intellectual outcome ranged from 45 to 103 (mean 77 ± 14) and was <85 in 62%. Movement disorders were found in 17 (47%) of the 36 tested patients. In females aged 12 years and older, primary ovarian insufficiency was diagnosed in 12 (71%) of the 17 patients. Significant differences in N -glycan peaks were found between controls and patients. However, no significant differences in either N -glycans or galactose-1-phosphate levels were found between patients with a poor (intellectual outcome < 85) and normal intellectual outcome (intellectual outcome ≥ 85), and with or without movement disorders or primary ovarian insufficiency. The variant patients detected by newborn screening, with previously unknown geno- and phenotypes and currently no long-term complications, demonstrated significantly lower galactose-1-phospate levels than classical patients ( P  < 0.0005). Qualitative analysis of the MRI's demonstrated brain abnormalities in 18 of the 21 patients, more severely in patients with a lower intellectual outcome and/or with movement disorders. This study demonstrates a large variability in clinical outcome, which varies from a below average intelligence, movement disorders and in females primary ovarian insufficiency to a normal clinical outcome. In our cohort of classical galactosemia patients, galactose-1-phosphate levels and N -glycan variations were not associated with clinical outcomes, but galactose-1-phosphate levels did differentiate between classical and variant patients detected by newborn screening. The correlation between brain abnormalities and clinical outcome should be further investigated by quantitative analysis of the MR images. The variability in clinical outcome necessitates individual and standardized evaluation of all classical galactosemia patients. Abstract : Patients with classical galactosemia frequently suffer from complications affecting the brain for which prognostic factors are lacking. In our cohort of classical galactosemia patients, we demonstrated a highly variable outcome, distinguished a subgroup of milder 'variant patients' and found an association between MRI abnormalities and lower intellectual outcomes and movement disorders. Graphical Abstract: